2019
DOI: 10.1007/s11356-019-06245-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of railways on bird diversity in farmland

Abstract: With a length exceeding 210,000 km in Europe, railways are common linear features dissecting landscapes. However, the impact of railway networks on biodiversity is equivocal. In this study, we investigated the effect of railway embankments on bird diversity components in an agricultural landscape in southern Poland. Forty transects including 20 along railways and 20 as controls in open fields were established. Birds were counted twice in 2009, and environmental characteristics were estimated for each transect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 93 publications
2
11
0
Order By: Relevance
“…The assessment of the bird diversity in the railway stations provided imperative information about the species assemblage patterns, variations in species composition, and species-specific abundance and richness in the station areas, much in support of the positive effects of railways on bird assemblages (Li et al 2010, Morelli et al 2014, Wiącek et al 2015, 2019, Kaiser-Bonk et al 2019. Variations in the bird species composition along the rural-urban gradient context remained similar to the observations made from Kolkata (Sengupta et al 2014, Pal et al 2019 and Amravati (Kale et al 2018a(Kale et al , 2018b, India.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The assessment of the bird diversity in the railway stations provided imperative information about the species assemblage patterns, variations in species composition, and species-specific abundance and richness in the station areas, much in support of the positive effects of railways on bird assemblages (Li et al 2010, Morelli et al 2014, Wiącek et al 2015, 2019, Kaiser-Bonk et al 2019. Variations in the bird species composition along the rural-urban gradient context remained similar to the observations made from Kolkata (Sengupta et al 2014, Pal et al 2019 and Amravati (Kale et al 2018a(Kale et al , 2018b, India.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, the railway network emerges as a prospective and perceived threat to the wildlife biota, including birds. However, the potential positive consequences of the railway network as well as the rail-associated construction structures on birds are increasingly appreciated (Li et al 2010, van der Ree et al 2011, Morelli et al 2014, Wiącek et al 2015, 2019, Kaiser-Bonk et al 2019. Some of the plausible positive effects of rail-associated structures includes the marginal vegetation along railways (bridges, shrubs etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More studies are needed to draw clear conclusions. It was recently found that the abundance of birds was not statistically different between along railways and away from railways in farmland landscape [156], suggesting that railway verges may be a suitable habitat for some vertebrate species. Bird species richness in railway embankments was even found to be higher than away from railways, probably because in agricultural landscapes railway verges are important remnants of diverse vegetation, increasing the number of available niches in the landscape [156] and because the noise disturbance due to trains passing at clear intervals is marginal [157].…”
Section: Powerline and Railway Verges May Constitute A Suitable Habitmentioning
confidence: 99%